Comparison of post-mortem radiologic modalities to evaluate suspected neck violence. (June 2020) - de Bakker, Henri M.; Olsthoorn, Priscilla C.; Soerdjbalie-Makoe, Vidija; de Bakker, Bernadette S.
Highlights: Three imaging modalities of the hyoid-larynx complex (HLC) were compared with autopsy. X-ray of the excised HLC best detected the number and locations of thyroid fractures. X-ray and CT of the explant scored better than PMCT for fractures in the hyoid bone. X-ray of the excised HLC is the best imaging modality to detect fractures of the HLC. We recommend to do autopsy and X-ray of the excised HLC in cases of neck violence. Abstract: Objective: Post-mortem computed tomography (PMCT) has become the standard imaging technique prior to forensic autopsy. Dedicated imaging of the excised hyoid-larynx complex (HLC) is often performed to diagnose fractures, which are indicative for violence on the neck. The aim of this study was to define which imaging technique present in our general hospital (in the absence of a micro-CT) is most suited to detect fractures in the HLC. Material and methods: 11 post-mortem cases with suspected violence on the neck were subjected to three imaging modalities: 1) hyoid-larynx reconstructions from the initial PMCT, 2) X-ray scan of the explant, and 3) CT scan of the explant. Each of these modalities were studied individually by three expert forensic radiologists for the presence of fractures in the hyoid bone and calcified thyroid cartilage. The results were then compared with the preliminary autopsy findings (i.e. manual palpation and inspection). Results: The use of X-ray proofed to be the superior technique to evaluate the number and locations of thyroid cartilage fractures within the excised HLC. To assess fractures in the hyoid bone, the X-ray and CT were considerably more reliable than reconstruction through PMCT. Conclusions: In the absence of micro-CT techniques and non-conclusive PMCT, X-ray scanning of the excised HLC is the recommended imaging modality to detect fractures of the HLC because of its high contrast resolution and multiple (8) projection directions. In order to distinguish between peri-mortem and post-mortem injury (vital sign), histological verification remains the golden standard.